Analisa Strategi E-Marketing Dinas Koperasi UKM Kota Medan terhadap UKM Binaan di Tengah Pandemi Covid-19 Tahun 2020 - Ida Lindiawati; R. Hamdani Harahap; Siti Mardiana (Universitas Medan Area, 2021)
The objectives of this study are to: 1) Analyze and explain the effectiveness of internet-based online marketing strategies for SME products, 2) Analyze and explain the implementation of internet-based online marketing strategies for SME products, 3) Analyze and describe the supporting factors for the success of internet-based online marketing strategies for SME products, and 4) Analyze and describe the factors inhibiting the success of the internet-based online marketing strategy for SME products. The results showed that the effectiveness of the internet-based online marketing strategy of the SME products assisted by the Medan City Cooperative Office was still not optimal. The causative factor for this is due to the limited promotional budget owned by the Medan City UKM Cooperative Office in 2020 as well as the refocusing policy. The implementation of an internet-based online marketing strategy for SME products guided by the Medan City UKM Cooperative Office in 2020 in the midst of the Covid-19 pandemic was implemented and complied with the principles of coordination, the idea of cooperation through BRI banks to open easy access to credit, cooperation with online businesses to build digital market place with Grabfood, providing a market place at Bukalapak. Barriers to training distance and high interest in participating in training were seen to be quite dominant.